2020
DOI: 10.26434/chemrxiv.12152970.v4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Predictive Model of the Temperature-Dependent Inactivation of Coronaviruses

Abstract: The COVID-19 pandemic has stressed healthcare systems and supply lines, forcing medical doctors to risk infection by decontaminating and reusing single-use medical personal protective equipment. The uncertain future of the pandemic is compounded by limited data on the ability of the responsible virus, SARS-CoV-2, to survive across various climates, preventing epidemiologists from accurately modeling its spread. However, a detailed thermodynamic analysis of experimental data on the inactivation of SARS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…We fit experimental data obtained from Chin et al 27 for SARS-CoV-2, as shown in Figure 1f, to find an activation energy of 132.6 kJ mol -1 and a natural log of the frequency factor, ln (𝐴), of 47.4. The correlation between the two fit parameters, 𝐸 𝑎 and ln (𝐴), follows a Meyer-Neldel rule that is suggestive of protein denaturation at high temperatures, 28 where x is position, t is time, and De is the dispersion coefficient.…”
Section: Thermal Inactivation Of Sars-cov-2mentioning
confidence: 93%
See 1 more Smart Citation
“…We fit experimental data obtained from Chin et al 27 for SARS-CoV-2, as shown in Figure 1f, to find an activation energy of 132.6 kJ mol -1 and a natural log of the frequency factor, ln (𝐴), of 47.4. The correlation between the two fit parameters, 𝐸 𝑎 and ln (𝐴), follows a Meyer-Neldel rule that is suggestive of protein denaturation at high temperatures, 28 where x is position, t is time, and De is the dispersion coefficient.…”
Section: Thermal Inactivation Of Sars-cov-2mentioning
confidence: 93%
“…Data reproduced from Chin et al27 (G) Thermal inactivation of SARS-CoV-2 is wellcharacterized, with first-order rate parameters following a Meyer-Neldel rule in agreement with other coronaviruses like the first severe acute respiratory syndrome coronavirus (SARS-CoV-1), middle east respiratory syndrome (MERS-CoV), transmissible gastroenteritis virus (TGEV), mouse hepatitis virus (MHV), and porcine epidemic diarrhea virus (PEDV). Data reproduced from Yap et al28 [Color figure can be viewed at wileyonlinelibrary.com]…”
mentioning
confidence: 99%